Large ionospheric disturbances produced by the HAARP HF facility. Issue 7 (21st July 2016) - Bernhardt, Paul A.; Siefring, Carl L.; Briczinski, Stanley J.; McCarrick, Mike; Michell, Robert G.
Abstract: The enormous transmitter power, fully programmable antenna array, and agile frequency generation of the High Frequency Active Auroral Research Program (HAARP) facility in Alaska have allowed the production of unprecedented disturbances in the ionosphere. Using both pencil beams and conical (or twisted) beam transmissions, artificial ionization clouds have been generated near the second, third, fourth, and sixth harmonics of the electron gyrofrequency. The conical beam has been used to sustain these clouds for up to 5 h as opposed to less than 30 min durations produced using pencil beams. The largest density plasma clouds have been produced at the highest harmonic transmissions. Satellite radio transmissions at 253 MHz from the National Research Laboratory TACSat4 communications experiment have been severely disturbed by propagating through artificial plasma regions. The scintillation levels for UHF waves passing through artificial ionization clouds from HAARP are typically 16 dB. This is much larger than previously reported scintillations at other HF facilities which have been limited to 3 dB or less. The goals of future HAARP experiments should be to build on these discoveries to sustain plasma densities larger than that of the background ionosphere for use as ionospheric reflectors of radio signals. Key Points: HAARP facility produces unique results Artificial plasma clouds are emission and optical signatures Future HAARP experiments are needed to explain physics